Erzielen Weine mit höherer Qualität höhere Preise? Eine hedonische Preisanalyse zur DLG-Bundesweinprämierung; Do High-quality Wines Capture Higher Prices? A Hedonic Price Analysis on DLG Quality Tests - Isabel Schaüfele; Roland Herrmann; Gergely Szolnoki (German Journal of Agricultural Economics (GJAE), 2016)
– With data from the Quality Tests by Deutsche Landwirtschafts-Gesellschaft (DLG) for wine, i.e. Deutsche Bundesweinpram̈ierung, we analyze to what extent quality awards lead to higher wine prices. The empirical analysis reveals that DLG Awards in Silver, Gold and Gold Extra are associated with statistically significant price premia. Apparently, a successful participation in the Quality Tests raises consumers' marginal willingness to pay for a wine and producers may realize higher net prices. It is crucial here how quality is communicated to buyers in the decision-making process. Price premia due to DLG awards suggest that it is more important to establish a reputation over time than just signaling quality by showing award labels on the bottle. The quantitative results show that quality grades, regional origin, grape variety, wine style and sweetness are further product characteristics that strongly affect wine prices due to their impacts on winegrowers' marginal costs and/or on consumer preferences.
Keywords: 330